Aldosterone Induces Vascular Damage: A Wave Reflection Analysis Study. Issue 3 (September 2019) - Hung, Chi-Sheng; Sung, Shih-Hsien; Liao, Che-Wei; Pan, Chien-Ting; Chang, Chin-Chen; Chen, Zheng-Wei; Wu, Vin-Cent; Chen, Chen-Huan; Cheng, Hao-Min; Lin, Yen-Hung
Abstract : Primary aldosteronism (PA) is hemodynamically independently associated with arterial wall stiffness as assessed by pulse wave velocity (PWV) compared with essential hypertension. Arterial wave reflection parameters derived from pulse wave analysis, such as forward and backward wave amplitudes (Pf and Pb), are promising vascular markers to predict cardiovascular outcomes in addition to PWV. These vascular parameters have never been studied in patients with PA before. In study part A, we prospectively enrolled 67 patients with PA and 132 patients with essential hypertension. In study part B, another 54 patients with PA were enrolled. Heart-carotid PWV was measured, and carotid pressure waveforms were recorded to calculate Pf, Pb, and augmentation index at baseline (part A and B) and 6 months after treatment (part B). The results showed that the patients with PA had significantly higher Pf ( P =0.001), Pb ( P =0.01), and PWV ( P =0.021) than the patients with essential hypertension. In univariate correlation analysis, both log Pf and Pb were significantly correlated with age, office blood pressure, serum potassium level, log PWV, and the presence of PA. However, only Pb was significantly correlated with log plasma renin activity and log aldosterone to renin ratio. In multivariate analysis, log Pf was significantly correlated with the presence of PA ( P =0.001), male sex, age, and mean arterial blood pressure. Pb was significantly correlated with the presence of PA ( P =0.031), age, and mean arterial pressure. Six months after treatment, Pf and Pb decreased significantly. In conclusion, the patients with PA had significantly increased wave reflections compared with the patients with essential hypertension. Our results provide clinical evidence of aldosterone-related extensive vascular dysfunction of the arterial system. Abstract : Supplemental Digital Content is available in the text.